Phoromorphs in ecomorphs system of soil animals - Жуков, О. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The aim of the present investigation is to reveal the role of phoromorphs of soil animals in the diatropic netwok defined by ecomorphic matrixes. Phoric communications create possibility of physical transport of objects, substance and energy both within one and between various biogeocoenoses. Active movement is specific feature of animals. Soil animals form ecological connections, promoting transferring of other live organisms, or can use other animals or plants for moving. Some groups of soil animals or act as active agents of movement of live organisms in a soil profile, or considerably assist this movement. On the other hand, in the geographical aspect moving soil animals on considerable distances by means of own adaptations is not probable. Therefore more mobile organisms on the surface of soil or in the air are the active factor of pedobionts moving. Adaptations for movement are the characteristic feature of active participation of a soil animal in phoric communications. Movement conditions in soil are so original, that have led to formation of special adaptations in many inhabitants of this environment. The soil as an inhabitancy, demands from animals living in it certain adaptations for movement. In the context of consortive organisation of animals groupings these adaptations have the interconnected character and have phoretic value, and ecological groups of soil animals on the basis of their phoretic features – phoromorphs can be allocated. The phoromorphic structure is the important functional feature of communities of soil animals as gives the information on prevailing directions of phoretic activity in corresponding ecological conditions.